2017
DOI: 10.1111/1744-9987.12579
|View full text |Cite
|
Sign up to set email alerts
|

Red Blood Cell Distribution Width Is Associated With All‐Cause and Cardiovascular Mortality in Hemodialysis Patients

Abstract: Red blood cell distribution width (RDW) is an index of red blood cell variability that is usually used to differentiate the cause of anemia. However, clinical evidence for the relationship between RDW and mortality in hemodialysis patients is still lacking. We performed a single center, prospective longitudinal study. During more than 5 years of follow-up in 80 patients undergoing maintenance hemodialysis, 34 patients (42.5%) died. In the Kaplan-Meier curve analyses, higher RDW levels (≥ 14.9%) were significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 26 publications
(28 reference statements)
0
11
0
Order By: Relevance
“…In recent studies, RDW has also been implicated in the clinical setting of kidney diseases. A retrospective cohort, recruited 109,675 adult maintenance HD patients in the United States, reported that baseline RDW is a stronger predictor of mortality than traditional laboratory markers of anemia [17]. A metaanalysis, incorporated 9 observational studies with a total of 117,047 subjects, suggested that high levels of baseline RDW probably increase the risk of all-cause mortality in CKD patients [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent studies, RDW has also been implicated in the clinical setting of kidney diseases. A retrospective cohort, recruited 109,675 adult maintenance HD patients in the United States, reported that baseline RDW is a stronger predictor of mortality than traditional laboratory markers of anemia [17]. A metaanalysis, incorporated 9 observational studies with a total of 117,047 subjects, suggested that high levels of baseline RDW probably increase the risk of all-cause mortality in CKD patients [19].…”
Section: Discussionmentioning
confidence: 99%
“…Elevated RDW is not only associated with enhancive destruction and ineffective production of erythrocyte, but also indicates the iron deficiency anemia, inflammation, and malnutrition status [9,10]. For the past few years, although the underlying mechanism is not well understood, studies have shown that RDW is closely related to the risk of adverse outcomes in multifarious populations, including patients with cardiovascular disease, sepsis, diabetes mellitus, and acute/chronic kidney disease, or even those undergoing hemodialysis (HD) and PD [9,[11][12][13][14][15][16][17][18][19][20]. The latest multi-center cohort [18], including 14,323 PD patients, suggested that the RDW of !16.5% (after adjustment of clinical and laboratory characteristics) had a 40% and 69% higher risk of death in baseline and time-varying analyses compared with the RDW of 14.5-15.5%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The present cost-effectiveness analysis based on the ICER calculated from the ASTRIO study results showed that FC was more cost-effective than non-iron-based phosphate binders in terms of overall drug costs and changes in RDW, which is associated with mortality in haemodialysis patients 19,26 . Interpreting this result in terms of both cost reduction and better health outcomes 27 indicated that FC was economically advantageous.…”
Section: Discussionmentioning
confidence: 79%
“…In HD group 3, this value was 15.08%, compared with 13.44% in the control healthy group. In their study on 80 CKD patients undergoing hemodialysis, Hirotaka and colleagues found that the mean value of RDW was 14.9% (10) .…”
Section: Discussionmentioning
confidence: 97%